Reinterpretasi Pasal 9 Konstitusi 1947 Jepang: Potensi Ancaman dalam Komitmen Jepang Pada War on Terror - Damartyas Murti Wredhanto; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2018)
International Security issue has been a huge concern to Japan under the administration of Shinzo Abe. After the demilitarization of the Japan by the United States and the allies on World War II, Japan can only rely on the United States military base in Okinawa, and some other kind of police to protect themselves. Japan's intend to strengthen its military capacity and power was outlawed due to Article 9 of the Japanese 1947 Constitution that restricts Japan to use any form of military power to solve any kind of dispute that taken place on their territory. The Constitution was made by the United States and the allies as the victorious side of the World War II to disarm all of Japan's military capacity and power. With that constitution (especially Article 9), Japan was changing from an expansionist-imperialist into a peaceful country that uses any form of negotiation to solve any kind of dispute that they've faced. But on 2014, Prime Minister Shinzo Abe and his administration unveils that reinterpretation of the Article 9 is happening and being discussed at the parliament to allow Japan's Self Defense Force (JSDF) (for the first time) helps the allies if they needed some, to support War on Terror propaganda by the United States.